Family Financial Education and Fintech as Determinants of Financial Behavior: The Mediating Role of Financial Literacy - Utami, Eristy Minda; Fatihat, Gita Genia; Wijaya, John Henry (ADPEBI International Journal of Business and Social Science, 2026)
Purpose – This study aims to examine family financial education and Financial Technology (Fintech) as determinants of financial behavior, with financial literacy serving as a mediating variable among university students at Universitas Widyatama. Methodology/approach – This study adopted a data-driven methodology, employing a structured survey administered to students who interact with Fintech platforms and receive financial guidance from their families. The gathered data were examined through Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the measurement framework and explore structural associations, including mediation roles. Findings – The results indicate that both family financial education and Fintech significantly enhance financial literacy. Financial literacy significantly predicts financial behavior. Family financial education exerts both direct and indirect effects on financial behavior, demonstrating partial mediation. In contrast, Fintech does not directly predict financial behavior but operates entirely through financial literacy, indicating full mediation. These findings suggest structurally distinct pathways through which social and technological factors shape financial behavior. Novelty/value – This study integrates financial socialization and digital financialization perspectives within a single framework, demonstrating that financial literacy is the key mechanism that transforms both early socialization and digital exposure into responsible financial behavior. The findings show that access to digital financial services alone does not ensure financial capability.